XGLM Model Scaling in Zero-Shot Cross-Lingual Educational Dialogue Act Classification - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 10 peer-reviewed papers addressing the following research question: How does the performance of XGLM models (564M vs. 1.7B) compare in zero-shot cross-lingual transfer for educational dialogue act classification on under-resourced languages like Indonesian versus. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 6.5/10. This report is
Machine-generated literature synthesis.